Endophytes: role in maintaining plant health under stress conditions - Karabulut, Fadime; Parray, Javid A.; Shafi, Nusrat; Ikram, Mohd (Elsevier, 2023)
Efforts are required to address the global threat posed by climate change-related irregular precipitation, temperature rise, and salinization of farmland. Abiotic stress has a negative impact on plants, reducing yields and hurting farmers. A variety of microorganisms constantly interact with plants. The ability of plant growth-promoting microorganisms, particularly endophytes, to minimize environmental stresses on crops without having negative effects has attracted attention in recent years. Endophytes are bacteria and fungi that live in healthy plant tissues, support plant growth under stress, and are useful in figuring out what factors encourage plant growth. Endophytes are crucial to the physiological and biological stages of plant development. While some endophytes have seed origins, it is known that the vast majority of plants have endophytes colonizing their roots, root collars, stems, and leaves, among other plant tissues. Endophytes derived from seeds can produce a range of phytohormones, enzymes, antimicrobial compounds, and other secondary metabolites that increase plant biomass and yield in the face of abiotic stresses. Endophyte bacteria play an important role in nitrogen fixation, play an important role in regulating plant physiology by promoting plant growth with the plant growth regulators they produce, and promote plant resistance in the presence of various abiotic stress conditions. Endophytes are also essential for sustainingly boosting agricultural productivity, reestablishing soil fertility, supplying food for the populace, and enhancing the ecosystem. Utilizing microbial inoculants that are friendly to the environment is one way to achieve this. In this chapter, endophytes are discussed in detail as they frequently provide novel methods for using biofertilizers, biopesticides, and endophytic inoculants in sustainable agriculture to reduce abiotic stresses in soil like salinity, cold, drought, and pH change. © 2024 Elsevier Inc. All rights reserved.
Keywords: abiotic stress; biocontrol; Endophytes; plant defense system; plant physiology